2022
DOI: 10.3389/fpsyg.2022.856063
|View full text |Cite
|
Sign up to set email alerts
|

Optimistic Environmental Messaging Increases State Optimism and in vivo Pro-environmental Behavior

Abstract: Despite recent empirical interest, the links between optimism and pessimism with pro-environmental behavior (PEB) remain equivocal. This research is characterized by a reliance on cross-sectional data, a focus on trait-level at the neglect of state-level optimism–pessimism, and assessments of retrospective self-reported ecological behavior that are subject to response bias. To attend to these gaps, 140 North American adults (Mage = 34; SD = 11.60; 44% female) were experimentally primed with bogus optimistic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In some cognitive conceptualizations, hope consists of clear goals, pathways to reach these goals, and agency thinking ( Snyder et al, 2001 ), which we did not focus on in this study. Therefore, in future studies it could be valuable to include either the emotion of hope (see Ojala, 2008 ) or some cognitive measure of climate hope (see Li and Monroe, 2019 ; Sangervo et al, 2022 ), or a more general trait or state measures of optimism ( Kaida and Kaida, 2019 ; MacKinnon et al, 2022 ). It could also be that, just as is the case with the emotion of climate hope, one needs to consider what sources people base their optimism on, since they can, respectively, be more constructive or less constructive, seen from an engagement perspective (see Ojala, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cognitive conceptualizations, hope consists of clear goals, pathways to reach these goals, and agency thinking ( Snyder et al, 2001 ), which we did not focus on in this study. Therefore, in future studies it could be valuable to include either the emotion of hope (see Ojala, 2008 ) or some cognitive measure of climate hope (see Li and Monroe, 2019 ; Sangervo et al, 2022 ), or a more general trait or state measures of optimism ( Kaida and Kaida, 2019 ; MacKinnon et al, 2022 ). It could also be that, just as is the case with the emotion of climate hope, one needs to consider what sources people base their optimism on, since they can, respectively, be more constructive or less constructive, seen from an engagement perspective (see Ojala, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…As to hope and optimism, their role in explaining climate engagement is unclear (see, e.g., Ojala, 2023 ). Both optimism as a personality trait ( Kaida and Kaida, 2019 ) and general state optimism ( MacKinnon et al, 2022 ) have been found to be positively related to pro-environmental behavior among adults. Regarding climate-related hope and optimism, that is, a view that humanity can fight climate change in a successful way, the correlation with climate engagement has been positive in some studies ( Feldman and Hart, 2018 ; Pihkala et al, 2022 ; Sangervo et al, 2022 ), but non-significant in some other studies ( Hornsey and Fielding, 2016 ; Wang and Chen, 2022 ).…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%